Internet das coisas no Brasil: Análise e recomendaç\~ao de políticas com ênfase no agronegócio - Luis Claudio Kubota; Mauricio Benedeti Rosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Unlike information and communication technologies from previous generations, which implementation was more restricted to the corporate world, the triad internet of things (IoT), artificial intelligence, and cloud and edge computing have use in a variety of human activities. If Brazil lost opportunities in previous decades in electronics, there are reasons for optimism regarding IoT. First, Brazil has a sectoral system of innovation with capacity to generate and implement related Technologies. The country has also developed a well designed plan and a good governance Methodology. Finally, several world class initiatives are a reality. The article brings a characterization of Iot in Brazil, composed of a bibliometric analysis, presentation of the National Plan of IoT and its relationship with the Brazilian Strategy of Digital Transformation, a Survey of IoT studies in the agrobusiness, an analysis of the sectoral policies related to the supply side of IoT, and an international comparison and cases of success in the implementation of the technology in the country.
Keywords: L63; L96; O38; 330; internet of things; ICT